رُؤية تَمَّام حَسان لأَنوَاع الكَلِمَات العَرَبِيَّةرُؤية تَمَّام حَسان لأَنوَاع الكَلِمَات العَرَبِيَّة - معمري, زينب; بديار, بشير (جامعة الوادي - University of Eloued, 2021)
نتناول في هذه الورقة البحثية رأي تمام حسان في تقسيم الكلمات العربية، ومنهجه وخلفياته في تقسيمه للكلمات، فقد اعتمد أسسا جديدة في تقسيمه ، باعتماده النظر في المبنى والمعنى معا في التفريق بين الأقسام، وزعم أن النحاة الأولون لم يراعوا هذه الأسس في تقسيمهم، ونقد تقسيمهم الثلاثي الذي رأى فيه قصورا وأنه لا يستوعب كل الكلمات العربية، فخلص إلى تقسيمه الجديد؛ ورأى أن أقسام الكلمة العربية سبعة: اسم وفعل وصفة وضمير وأداة وظرف وخالفة. وهي الأقسام التي ارتضاها تمام حسان بديلا عن التقسيم القديم، ويرى في تقسيمه أنه مستوعب لكل الكلمات العربية. This study tackles with the Tammam Hassan’s perspective for classifying Arabic words, his approach and backgrounds in his classification of words. Thus, Tammam Hassan adopts new principles based on the structure and meaning together for differentiating between sections of words. Because of this, he claims that the first grammarians did not observe these principles in their classifications, and then he criticized their triple division. He views that it contains deficiencies and did not cover all the Arabic words. Therefore, He suggests a new division, which includes seven parts: noun, verb, adjective, pronoun, tool, adverb and succession. In sum, Tamam Hassan argures that these parts are an alternative for the old division. Hence, this division includes all the Arabic words.
مقال
Keywords: تمام حسان،منهجه ، التقسيم الثلاثي للكلم، التقسيم السباعي للكلم، المبنى ، المعنى; Tamam Hassan, His method, Triple division of the word, Seven division of the word, the building, the meaning